2022
DOI: 10.1021/acs.energyfuels.2c02780
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Methane Hydrate Formation Using Biofriendly Amino Acids for Natural Gas Storage Applications: Kinetic and Morphology Insights

Abstract: Solidified natural gas is an appealing option for storing natural gas in the form of clathrate hydrates. However, it has some limitations, particularly the slow rate of hydrate formation and the requirement for severe operating conditions. To overcome these constraints, one approach is to introduce promoters into the system to enhance the hydrate formation rate. Amino acids have been reported as kinetic promoters with the potential to improve the methane hydrate formation. In this work, the effect of three dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
4
1
0
Order By: Relevance
“…While increasing the MEG content from 0.1 to 25 wt %, the nucleation temperature was substantially reduced. With 20 and 25 wt % MEG, nucleation temperature was reduced by 10–12 °C with respect to the baseline data, which corroborates well with the nucleation temperature measured for synthetic natural gas hydrates in the literature . As expected, BGE and caprolactam (Cap.)…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…While increasing the MEG content from 0.1 to 25 wt %, the nucleation temperature was substantially reduced. With 20 and 25 wt % MEG, nucleation temperature was reduced by 10–12 °C with respect to the baseline data, which corroborates well with the nucleation temperature measured for synthetic natural gas hydrates in the literature . As expected, BGE and caprolactam (Cap.)…”
Section: Resultssupporting
confidence: 90%
“…Another possible reason of gas bubble formation would be the gas dissolution in the liquid phase. Similar characteristics of hydrate bubble formation and rapid hydrate were reported by Chaovarin et al in the presence of amino acids . Moreover, the hydrate morphology observed in the current work also support the gas-adsorbing inhibition mechanism for KHIs proposed based on the molecular dynamic simulation studies, wherein KHIs were found to have an excellent adsorption ability of methane gas and diminish the supersaturation of methane in the liquid phase while facilitating the formation of gas bubbles and inhibiting the hydrate growth …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…To ensure the condition of CH 4 hydrate stability zone and reduce the disturbance of gas/water injection, the initial temperature and pressure was set as 1 °C and 5 MPa, respectively, as given in Figure . The hydrate formation kinetics and morphology are of interest to researchers considering their significance in hydrate exploitation and application. When juvenile water is encompassed by free CH 4 gas, the hydrate mass nucleates and grows along the interface of gas and water until the morphology of grain cementing or coating is formed with most part of the liquid being consumed. , The excess water method (EW) is defined as the method of preparation of the above-mentioned grain-cementing hydrate-bearing sediments plus the water saturation process. Another interpretation was that dissolved gas is origin of pore-filling hydrate; meanwhile, the CT scan patterns prove that a cemented hydrate lattice in a water-saturated environment could be converted to an isolated hydrate through phase equilibrium disturbance by water flush and temperature regulation, indicating the occurrence of a pore-filling hydrate (Choi et al; Lei et al; Sadeq et al; Spangenberg et al). ,,,, Therefore, the temperature was risen and dropped back to the initial temperature with constant pressure (see Figure d), which could lead to hydrate reformation and water migration, namely, excess water method plus hydrate dissociation and reformation (EWDR).…”
Section: Methodsmentioning
confidence: 99%